Visual performance standards for virtual and augmented reality - Penczek, John (Frontiers in Virtual Reality, 2025)
Extended reality devices are enabling new approaches and procedures in the medical field. However, many in the medical community are unfamiliar with these technologies and how to evaluate them for a given application. This article presents an overview of the available international visual performance standards for virtual and augmented reality devices to better inform users and developers on the critical metrics and methods commonly used to assess the devices. These standards provide guidance to minimize collisions and falls during casual use, reduce visual discomfort and fatigue during extended use in areas such as pain management, training, and surgery, and increase efficiency and outcomes through improved image quality and readability of visual information. The article is intended to assist users with identifying which visual performance parameters may be critical for their application and directs the user to the relevant standards where the detailed evaluation methods can be obtained.